1998
DOI: 10.1038/sj.onc.1202021
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Fas-mediated apoptosis: activation of Caspase 3 is regulated by cell cycle regulator p21WAF1 and IAP gene family ILP

Abstract: The death receptor Fas transduces apoptotic death signaling mediated by caspases. In the present study, human hepatoma HepG2 cells showed the Fas-mediated apoptosis mediated by caspase, especially caspase 3, only in the presence of actinomycin D. Interestingly, cytosolic proteins extracted from intact HepG2 cells induced caspase 3 inactivation. Our results reveal that this inactivation was triggered by the direct inhibition of activated caspase 3 by IAP gene family ILP. In addition, a 53 kDa protein was co-imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
278
1
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 323 publications
(294 citation statements)
references
References 23 publications
14
278
1
1
Order By: Relevance
“…One of the plausible explanations is that antiapoptotic mechanisms such as reduced expression of Fas and expression of antiapoptotic proteins, for example, bcl-2 or XIAP, in addition to survivin or receptormediated survival signals are involved in the progression of antiapoptosis of HCC cells. [29][30][31][32] The findings of both our in vitro and in vivo studies were in good agreement; this confirmed that stable knockdown of survivin abrogated its function in cell cycle regulation, and although it cannot induce spontaneous apoptosis directly and immediately, it sensitizes HCC cells to apoptotic stimuli. Most importantly, our result was consistent with the results of a previous clinical study that survivin expression in HCC tissues strongly correlated with the proliferation index, but did not significantly correlate with the apoptosis index.…”
Section: Discussionsupporting
confidence: 77%
“…One of the plausible explanations is that antiapoptotic mechanisms such as reduced expression of Fas and expression of antiapoptotic proteins, for example, bcl-2 or XIAP, in addition to survivin or receptormediated survival signals are involved in the progression of antiapoptosis of HCC cells. [29][30][31][32] The findings of both our in vitro and in vivo studies were in good agreement; this confirmed that stable knockdown of survivin abrogated its function in cell cycle regulation, and although it cannot induce spontaneous apoptosis directly and immediately, it sensitizes HCC cells to apoptotic stimuli. Most importantly, our result was consistent with the results of a previous clinical study that survivin expression in HCC tissues strongly correlated with the proliferation index, but did not significantly correlate with the apoptosis index.…”
Section: Discussionsupporting
confidence: 77%
“…Cytoplasmic p21 can interact with, and thereby inactivate, multiple pro-apoptotic proteins such as SAPK (also known as JNK) 91 , pro-caspase 3 (REF. 92) and ASK1 (apoptosissignal-regulating kinase 1, also known as mitogenactivated protein kinase kinase kinase 5 (MAP3K5)) 93,94 . Cytoplasmic localization of p21 has been reported to correspond with a poor clinical outcome of patients with breast cancer 95,96 , which could therefore be explained by the observation that besides losing its CDK-inhibitory function, cytoplasmic p21 also gains anti-apoptotic functions 93,94 .…”
Section: Is P21 Required For Oncogenic Transformation?mentioning
confidence: 99%
“…Moreover, it was recently shown that in cultured dermal fibroblasts, the lack of MIF is associated with a reduced nuclear localization of p21 (Taranto et al, 2009), a cyclin-dependent kinase inhibitor (1A) that participates in cell-cycle arrest, suggesting the involvement of MIF in p53-independent mechanisms. Apart from its function in the cell cycle, there is evidence that p21 is a direct inhibitor of apoptosis (Suzuki et al, 1998). Moreover, Harms et al (2007) show that activation of p21 via phosphorylation and translocation into the cytoplasm in neurons prevents apoptosis.…”
Section: Cell Death Promoting Action Of Macrophage Migration Inhibitomentioning
confidence: 99%